Proposal of a Framework of Implicit and Explicit Atitudes in Retail - Bizarrias, Flavio Santino (2017)
Dual attitudes, one more refletive (conscious) and one more impulsive (unconscious, or automatic) can be developed in relation to the same object of attitude. At the same time, most retail consumer behavior research studies marketing and environmental influences on the consumer, and few studies look at the influences consumers themselves exert on each other. Retailing is a shared space in which dual attitudes can be observed, under social influences. This paper proposes a conceptual model for the study of consumer phenomena in retail that are subject to divergence of conscious and unconscious evaluations of the consumers. We also establish theoretical propositions based on the conceptual model in a field of research that is still little developed in the scope of marketing. Add to this the potential of the phenomena studied through dual processes of formation and attitude change to produce complementary or even different conclusions for researchers and managers.